A recombinant collagen type III bioadhesive and its preparation method and application

CN122955013APending Publication Date: 2026-10-23SHANDONG YITENON BIOTECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611441861.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-17
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0004]有鉴于此,本发明提供了一种重组III型胶原蛋白生物粘合剂及其制备方法和应用,通过构建苯硼酸修饰γ-聚谷氨酸、特定序列重组III型胶原蛋白与聚乙烯醇的三组分动态交联体系,旨在解决现有生物粘合剂难以兼具快速温和成胶、湿面强粘附、高密封性能与良好生物相容性的问题,以满足微创术后创面密封与无缝合修复的临床需求

Benefits of technology

本发明通过采用苯硼酸修饰γ-聚谷氨酸、特定序列重组III型胶原蛋白与聚乙烯醇的三组分体系,在无需外加光照或化学交联剂的温和条件下即可快速凝胶化,解决了现有天然蛋白类粘合剂成胶慢、湿态粘附弱的问题;同时,重组III型胶原蛋白的引入赋予粘合剂优异的细胞相容性,克服了化学合成类粘合剂细胞毒性高的缺陷;苯硼酸修饰γ-聚谷氨酸与聚乙烯醇之间形成的动态共价键赋予粘合剂湿面强粘附能力,重组III型胶原蛋白参与构建的物理交联网络增强了凝胶内聚力。实验数据表明,该粘合剂在湿润组织表面的粘附强度可达50 kPa以上,爆破压力可达100 mmHg以上,显著优于市售纤维蛋白胶和氰基丙烯酸酯,且L929细胞存活率测试显示其细胞相容性显著优于氰基丙烯酸酯类粘合剂,能够有效满足微创术后创面密封对于快速固化、湿态粘附和生物安全性的综合要求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122955013A_ABST
    Figure CN122955013A_ABST
Patent Text Reader

Abstract

The application discloses a kind of recombinant collagen type III biological adhesive and its preparation method and application, belong to the technical field of biomedical materials.The recombinant collagen type III biological adhesive provided by the application is obtained by gelation after the first component and the second component are mixed;The first component includes phenyl boronic acid modified gamma-polyglutamic acid and recombinant collagen type III;The second component includes polyvinyl alcohol;The phenyl boronic acid modified gamma-polyglutamic acid is prepared by grafting 3-aminophenyl boronic acid to gamma-polyglutamic acid by amidation reaction;The amino acid sequence of the recombinant collagen type III is shown as SEQ ID NO:1.The biological adhesive prepared by the application can effectively meet the comprehensive requirements of rapid solidification, wet adhesion and biological safety for wound sealing after minimally invasive surgery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of biomedical materials technology, and in particular to a recombinant type III collagen bioadhesive, its preparation method, and its application. Background Technology

[0002] In minimally invasive surgeries such as thoracoscopic wedge resection of the lung and laparoscopic partial hepatectomy, postoperative wound leakage, bleeding, or effusion are common complications. Traditional repair methods mainly rely on mechanical sutures or physical covering materials. However, mechanical sutures are prone to needle hole leakage and can easily cause cutting or tearing of fragile tissues such as edema and emphysema; physical covering materials lack in-situ adhesion to dynamically moist wound surfaces, making it difficult to maintain stable adhesion and a lasting seal.

[0003] Existing biological tissue adhesives are mainly classified into natural protein-based, chemically synthesized, and photocurable hydrogel-based adhesives. While natural protein-based adhesives exhibit good biocompatibility, they generally suffer from slow gelation rates and insufficient wet adhesion strength, making it difficult to achieve rapid and stable adhesion in moist and dynamic wound environments. Chemically synthesized adhesives, although possessing strong adhesion, often pose cytotoxic risks, and their degradation products may trigger inflammatory responses. Photocurable hydrogel systems require external light source irradiation, limiting their operational conditions and making them unsuitable for minimally invasive surgical scenarios such as deep laparoscopic procedures. Furthermore, collagen-based adhesives typically have poor mechanical properties, and their adhesion strength rapidly diminishes in wet environments, making them unsuitable for use as standalone sealing materials. Summary of the Invention

[0004] In view of this, the present invention provides a recombinant type III collagen bioadhesive, its preparation method and application. By constructing a three-component dynamic crosslinking system of phenylboronic acid-modified γ-polyglutamic acid, specific sequence recombinant type III collagen and polyvinyl alcohol, it aims to solve the problem that existing bioadhesives are difficult to combine rapid and mild gelation, strong adhesion on wet surfaces, high sealing performance and good biocompatibility, so as to meet the clinical needs of wound sealing and suture repair after minimally invasive surgery.

[0005] In a first aspect, the present invention provides a recombinant type III collagen bioadhesive, which is obtained by gelling a mixture of a first component and a second component; The first component comprises phenylboronic acid-modified γ-polyglutamic acid and recombinant type III collagen; The second component includes polyvinyl alcohol; The phenylboronic acid-modified γ-polyglutamic acid was prepared by grafting 3-aminophenylboronic acid onto γ-polyglutamic acid via an amidation reaction; the amino acid sequence of the recombinant type III collagen is shown in SEQ ID NO: 1.

[0006] Preferably, in the first component, the concentration of phenylboronic acid-modified γ-polyglutamic acid is 20-60 mg / mL, and the concentration of recombinant type III collagen is 1-15 mg / mL.

[0007] Preferably, the concentration of polyvinyl alcohol in the second component is 5-15 wt%.

[0008] Secondly, the present invention provides a method for preparing the above-mentioned recombinant type III collagen bioadhesive, comprising the following steps: Phenylboronic acid-modified γ-polyglutamic acid and recombinant type III collagen were dissolved in the first buffer solution to obtain the first component; Polyvinyl alcohol was dissolved in the second buffer solution and heated and stirred until completely dissolved to obtain the second component; The first component and the second component are mixed and allowed to gel at rest to obtain the recombinant type III collagen bioadhesive.

[0009] Preferably, the first buffer and the second buffer are each independently selected from at least one of phosphate buffer (PBS), 4-hydroxyethylpiperazine ethanesulfonic acid (HEPES) buffer or tris(hydroxymethyl)aminomethane hydrochloride (Tris-HCl) buffer; the pH of the first buffer and the second buffer is 7.2 to 7.6.

[0010] Preferably, the preparation method of the phenylboronic acid modified γ-polyglutamic acid is as follows: γ-polyglutamic acid is dissolved in a solvent, activated by adding an activator, and then 3-aminophenylboronic acid or its salt is added for amidation reaction. After dialysis and freeze drying, phenylboronic acid modified γ-polyglutamic acid is obtained.

[0011] Further, the mass ratio of γ-polyglutamic acid and 3-aminophenylboronic acid or their salts is 1:(0.6~1.2); the activator is 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC·HCl) and N-hydroxysuccinimide (NHS); the mass ratio of γ-polyglutamic acid, EDC·HCl and NHS is 1:(0.8~1.2):(0.4~0.8).

[0012] Furthermore, the amidation reaction takes 15-30 h, the amidation reaction temperature is 15-40 °C, and the amidation reaction pH is 6.2-6.8; the amidation reaction is carried out under light-protected conditions.

[0013] Preferably, the mixing volume ratio of the first component to the second component is 1:(0.8~1.2).

[0014] Thirdly, the present invention provides the application of the above-mentioned recombinant type III collagen bioadhesive or the recombinant type III collagen bioadhesive prepared by the above-mentioned preparation method in the preparation of minimally invasive postoperative tissue sealing products.

[0015] Compared with the prior art, the present invention has achieved the following beneficial effects: This invention utilizes a three-component system of phenylboronic acid-modified γ-polyglutamic acid, specific-sequence recombinant type III collagen, and polyvinyl alcohol. This system enables rapid gelation under mild conditions without the need for external light or chemical cross-linking agents, solving the problems of slow gelation and weak wet adhesion of existing natural protein adhesives. Simultaneously, the introduction of recombinant type III collagen endows the adhesive with excellent cell compatibility, overcoming the high cytotoxicity of chemically synthesized adhesives. The dynamic covalent bonds formed between phenylboronic acid-modified γ-polyglutamic acid and polyvinyl alcohol impart strong adhesion to wet surfaces, while the physical cross-linking network constructed by recombinant type III collagen enhances gel cohesion. Experimental data show that the adhesive achieves an adhesion strength of over 50 kPa and a burst pressure of over 100 mmHg on moist tissue surfaces, significantly superior to commercially available fibrin glue and cyanoacrylate. Furthermore, L929 cell viability testing demonstrates significantly better cell compatibility than cyanoacrylate adhesives, effectively meeting the comprehensive requirements of rapid curing, wet adhesion, and biocompatibility for wound sealing after minimally invasive surgery. Attached Figure Description

[0016] The accompanying drawings, which form part of this specification, are used to provide a further understanding of the invention. The illustrative embodiments and descriptions of the invention are used to explain the invention and do not constitute an undue limitation thereof. Obviously, those skilled in the art can obtain other drawings based on these drawings without any inventive effort.

[0017] Figure 1 These are macroscopic photographs of the recombinant type III collagen bioadhesive prepared in Example 2 of the present invention; wherein, A is a photograph of the initial mixing, B is a photograph of the state after being laid flat and left to stand for about 5 seconds, and C is a photograph of the state of the bioadhesive as it is bent by a finger. Figure 2 This is a macroscopic photograph of the mixture after the first component and the second component are mixed evenly in equal volumes in Comparative Example 1 of this invention. Figure 3 These are scanning electron microscope images of the recombinant type III collagen bioadhesive prepared in Example 2 of this invention in its freeze-dried state. Figure 4 These are the shear adhesion strength test results of the bio-adhesives in Examples 1-4 and Comparative Example 3 of the present invention; Figure 5These are the burst pressure test results of the adhesives in Examples 1-4 and Comparative Examples 3-5 of the present invention; Figure 6 These are the cell viability test results of the adhesives in Examples 1-4 and Comparative Examples 3-5 of this invention. Detailed Implementation

[0018] It should be noted that the following detailed descriptions are exemplary and intended to provide further illustration of the invention. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.

[0019] In the description of this invention, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated.

[0020] The terms “including,” “comprising,” and any variations thereof are generally understood to be open-ended and non-restrictive, and do not exclude other elements or steps not stated therein, unless otherwise specifically stated or understood from the context.

[0021] The term “and / or” includes any and all combinations of the related listed items. For example, “A and / or B” can mean three cases: A alone, A and B together, or B alone.

[0022] It should be understood that the order of the steps or the order in which certain actions are performed is not important as long as the invention remains operational. Furthermore, two or more steps or actions can be performed simultaneously.

[0023] In minimally invasive surgeries such as thoracoscopic wedge resection of the lung and laparoscopic partial hepatectomy, postoperative wound leakage, bleeding, or effusion are common complications. Traditional mechanical suturing is difficult to avoid needle hole leakage and can easily cause cutting or tearing of fragile tissues such as those with edema or emphysema. Physical covering materials lack in-situ adhesion to dynamically moist wound surfaces, making it difficult to maintain stable adhesion and a lasting seal. Among existing biological tissue adhesives, natural protein adhesives have slow gelation and weak wet adhesion, chemically synthesized adhesives pose cytotoxic risks, and photocurable hydrogels have limited operating conditions. None of these can simultaneously meet the comprehensive requirements of rapid gelation, strong wet adhesion, high sealing performance, and good biocompatibility. Based on this, the present invention provides a recombinant type III collagen bioadhesive, its preparation method, and its application.

[0024] In a first aspect, the present invention provides a recombinant type III collagen bioadhesive.

[0025] In some embodiments of the present invention, the recombinant type III collagen bioadhesive is obtained by gelling a mixture of a first component and a second component; the first component includes phenylboronic acid-modified γ-polyglutamic acid and recombinant type III collagen; the second component includes polyvinyl alcohol; the phenylboronic acid-modified γ-polyglutamic acid is obtained by grafting 3-aminophenylboronic acid onto γ-polyglutamic acid via an amidation reaction; the amino acid sequence of the recombinant type III collagen is shown in SEQ ID NO: 1.

[0026] This invention uses phenylboronic acid-modified γ-polyglutamic acid (PBA-γ-PGA) as the first core component. γ-Polyglutamic acid is an anionic polyamino acid composed of D-glutamic acid and L-glutamic acid linked by amide bonds. Its molecular chain contains a large number of carboxyl side groups, which can serve as active sites for chemical modification. This invention grafts 3-aminophenylboronic acid onto the carboxyl side groups of γ-polyglutamic acid through an amidation reaction to obtain phenylboronic acid-modified γ-polyglutamic acid. Under physiological pH conditions, the phenylboronic acid groups can reversibly form borate ester dynamic covalent bonds with the diol groups on the polyvinyl alcohol molecular chain. This dynamic covalent bond endows the hydrogel with both rapid cross-linking and curing ability and good reversibility and self-healing properties, thereby overcoming the shortcomings of traditional natural protein adhesives, such as slow gelation speed and weak wet adhesion.

[0027] The amino acid sequence of the recombinant type III collagen used in this invention is shown in SEQ ID NO: 1. The recombinant type III collagen is preferably prepared through genetic engineering expression, resulting in a well-defined sequence and high batch stability, thus avoiding the potential risks of viral transmission and immunogenicity associated with traditional animal-derived collagen. In the system of this invention, the recombinant type III collagen exists in a free, unmodified form, participating as an independent structural component in the formation of the hydrogel network. Its abundant amino and carboxyl groups on its molecular chain can form non-covalent bonds such as hydrogen bonds and electrostatic interactions with groups on the surface of moist tissue, enhancing the adhesion between the adhesive and the tissue interface. Simultaneously, the recombinant type III collagen retains the cell-binding sites of natural collagen, which is beneficial for maintaining excellent cell compatibility and can provide a suitable microenvironment for in-situ repair and healing of wound tissue.

[0028] This invention uses polyvinyl alcohol (PVA) as the core component of the second part. PVA is a water-soluble synthetic polymer containing numerous secondary hydroxyl groups (diol groups) on its molecular chain. Under physiological pH conditions, it can reversibly form dynamic covalent bonds with phenylboronic acid groups, thus acting as crosslinking nodes to participate in the construction of the three-dimensional network structure of the hydrogel. Furthermore, PVA molecular chains can form physically crosslinked regions through hydrogen bonding, further enhancing the cohesiveness and mechanical strength of the hydrogel. PVA also possesses good biocompatibility and flexibility, and its introduction helps improve the mechanical and handling properties of the adhesive.

[0029] In some embodiments of the present invention, the concentration of phenylboronic acid-modified γ-polyglutamic acid in the first component is 20-60 mg / mL, for example, it can be any one value or any two values ​​from 20 mg / mL, 25 mg / mL, 30 mg / mL, 35 mg / mL, 40 mg / mL, 45 mg / mL, 50 mg / mL, 55 mg / mL or 60 mg / mL, preferably 35-45 mg / mL, more preferably 40 mg / mL. The concentration of the recombinant type III collagen is 1-15 mg / mL, for example, it can be any one value or any two values ​​from 1 mg / mL, 2 mg / mL, 3 mg / mL, 4 mg / mL, 5 mg / mL, 6 mg / mL, 7 mg / mL, 8 mg / mL, 9 mg / mL, 10 mg / mL, 11 mg / mL, 12 mg / mL, 13 mg / mL, 14 mg / mL or 15 mg / mL, preferably 4-10 mg / mL, more preferably 5 mg / mL. In the second component, the concentration of polyvinyl alcohol is 5 to 15 wt%, for example, it can be any one value or any two values ​​from 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, 10 wt%, 11 wt%, 12 wt%, 13 wt%, 14 wt% or 15 wt%, preferably 8 to 12 wt%, more preferably 10 wt%.

[0030] It should be noted that there is a synergistic effect between the concentration of phenylboronic acid-modified γ-polyglutamic acid and the concentration of recombinant type III collagen. When the concentration of recombinant type III collagen is too low, the wet adhesion strength and cell compatibility of the adhesive decrease significantly; when the concentration of recombinant type III collagen is too high, the collagen is difficult to completely dissolve, the solution becomes turbid and produces particulate precipitates, and it cannot form a homogeneous system to participate in the subsequent gelation process. When the concentration of phenylboronic acid-modified γ-polyglutamic acid is too low, the cross-linking density is insufficient, and the mechanical strength and sealing performance of the adhesive decrease; when the concentration is too high, the excessive cross-linking density leads to the gel network becoming brittle, and the adhesion strength and burst pressure decrease.

[0031] In some embodiments of the present invention, the first component and the second component are preferably present in separate packages. Separate packaging of the first and second components improves the product's storage stability; they can be taken out and mixed as needed, making the process simple and suitable for immediate clinical use.

[0032] In some embodiments of the present invention, the recombinant type III collagen bioadhesive possesses a dual-network structure where dynamic covalent bonds and physical crosslinks coexist. Specifically, phenylboronic acid-modified γ-polyglutamic acid forms a dynamic covalent bond with the diol group on polyvinyl alcohol, constituting a first crosslinking network; the recombinant type III collagen molecular chains and other components form a second crosslinking network through physical forces such as hydrogen bonds and electrostatic interactions. This dual-network structure endows the adhesive with excellent mechanical properties and structural stability.

[0033] Secondly, the present invention provides a method for preparing the above-mentioned recombinant type III collagen bioadhesive.

[0034] In some embodiments of the present invention, the preparation method includes the following steps: dissolving phenylboronic acid-modified γ-polyglutamic acid and recombinant type III collagen in a first buffer solution to obtain a first component; dissolving polyvinyl alcohol in a second buffer solution and heating and stirring until completely dissolved to obtain a second component; mixing the first component and the second component and allowing them to stand and gel to obtain the recombinant type III collagen bioadhesive.

[0035] The preparation method of this invention employs a step-by-step preparation and immediate mixing strategy. Phenylboronic acid-modified γ-polyglutamic acid and recombinant type III collagen are dissolved together in a first buffer solution, coexisting in a physical blend without chemical reaction. Polyvinyl alcohol is dissolved separately in a second buffer solution, and high-temperature heating promotes the full extension and dissolution of the polyvinyl alcohol molecular chains. During use, the first and second components are mixed in proportion. Under physiological pH conditions, the phenylboronic acid groups and the diol groups of polyvinyl alcohol spontaneously form dynamic covalent bonds of borate esters, accompanied by physical cross-linking effects such as hydrogen bonding. The system gradually loses its fluidity from a flowing liquid and forms a gel, i.e., gelation occurs. The entire process requires no external cross-linking agent, no light exposure, and no heating; the operating conditions are mild, making it particularly suitable for immediate use in minimally invasive surgical scenarios.

[0036] In some embodiments of the present invention, the first buffer and the second buffer are each independently selected from at least one of phosphate-buffered saline (PBS), 4-hydroxyethylpiperazine ethanesulfonic acid (HEPES) buffer, or tris(hydroxymethyl)aminomethane hydrochloride (Tris-HCl) buffer; the pH of the first buffer and the second buffer is 7.2 to 7.6. The pH of the first buffer can be 7.2, 7.3, 7.4, 7.5, or 7.6, preferably pH 7.4. All of the above buffers have good biocompatibility and can provide a stable acid-base environment within the physiological pH range, which is beneficial to the formation and maintenance of the dynamic covalent bond of phenylboronic acid-diol.

[0037] In some embodiments of the present invention, the preparation method of phenylboronic acid modified γ-polyglutamic acid is as follows: γ-polyglutamic acid is dissolved in a solvent, activated by adding an activator, and then 3-aminophenylboronic acid or its salt is added for amidation reaction. After dialysis and freeze-drying, phenylboronic acid modified γ-polyglutamic acid is obtained.

[0038] Specifically, γ-polyglutamic acid is dissolved in a suitable solvent (such as water) to prepare a solution of appropriate concentration. An activator is added for activation treatment; the activator converts the carboxyl groups on the side chains of γ-polyglutamic acid into active ester intermediates, facilitating subsequent amidation with the amino group of 3-aminophenylboronic acid. The activation reaction is usually carried out at room temperature. After activation, 3-aminophenylboronic acid or 3-aminophenylboronic acid salt solid powder is added, and an amidation reaction is carried out under weakly acidic conditions. After the reaction is complete, the reaction solution is transferred to a dialysis bag and dialyzed against acidic deionized water to remove unreacted small molecules and byproducts. Dialysis is then continued in deionized water, and finally, freeze-drying yields a white flocculent or sponge-like solid, which is phenylboronic acid-modified γ-polyglutamic acid.

[0039] In some embodiments of the present invention, the activator is 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC·HCl) and N-hydroxysuccinimide (NHS); the mass ratio of γ-polyglutamic acid, EDC·HCl and NHS is 1 : (0.8~1.2) : (0.4~0.8), more preferably 1 : (0.9~1.1) : (0.5~0.7). EDC, as a carboxyl activator, reacts with the carboxyl group of the γ-polyglutamic acid side chain to form an active O-acyl isourea intermediate; NHS, as a stabilizer, reacts with the above intermediate to form a relatively stable NHS ester intermediate, thereby improving the efficiency and yield of the amidation reaction and suppressing the occurrence of side reactions.

[0040] In some embodiments of the present invention, the mass ratio of γ-polyglutamic acid to 3-aminophenylboronic acid or its salt is 1:(0.6~1.2). The mass ratio of γ-polyglutamic acid to 3-aminophenylboronic acid can be any single value or a range of any two values ​​from 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1.0, 1:1.1 or 1:1.2; preferably 1:(0.8~0.9).

[0041] In some embodiments of the present invention, the amidation reaction time is 15-30 h, for example, any one or any two values ​​from 15 h, 18 h, 20 h, 22 h, 24 h, 26 h, 28 h, or 30 h, preferably 20-28 h, more preferably 24 h. The amidation reaction temperature is 15-40 °C, for example, any one or any two values ​​from 15 °C, 20 °C, 25 °C, 30 °C, 35 °C, or 40 °C, preferably room temperature. The amidation reaction pH is 6.2-6.8, for example, any one or any two values ​​from 6.2, 6.3, 6.4, 6.5, 6.6, 6.7, or 6.8, preferably 6.5. The amidation reaction is carried out under light-protected conditions, which helps reduce the photo-oxidative degradation of 3-aminophenylboronic acid and ensures efficient reaction.

[0042] In some embodiments of the present invention, the dialysis is performed using a dialysis bag with a molecular weight cutoff of 3500 Da. Dialysis is carried out in deionized water containing 0.005~0.02 M HCl for 1 day, followed by dialysis in deionized water for 2 days. The dialysate is changed every 6~10 hours, for a total of 8 or more changes. The HCl-containing dialysate helps maintain the solubility of phenylboronic acid-modified γ-polyglutamic acid and prevents its precipitation. After dialysis, the dialysate is transferred to a lyophilization container, pre-frozen at -80°C to -20°C, and then dried in a freeze dryer to constant weight, yielding a white flocculent or sponge-like solid.

[0043] In some embodiments of the present invention, the mixing volume ratio of the first component to the second component is 1:(0.8~1.2), for example, it can be any one value or a range of any two values ​​among 1:0.8, 1:0.85, 1:0.9, 1:0.95, 1:1.0, 1:1.05, 1:1.1, 1:1.15 or 1:1.2; preferably 1:1.

[0044] In some embodiments of the present invention, the static gelation time is 5-100 s, preferably 5-60 s. This rapid gelation characteristic allows the adhesive to quickly solidify into a sealing layer within the surgical procedure time, meeting the clinical need for ease of operation.

[0045] In some embodiments of the present invention, the polyvinyl alcohol is dissolved at a temperature of 90-100°C and for a time of 4-8 hours. The dissolution temperature can be 90°C, 92°C, 94°C, 95°C, 96°C, 98°C, or 100°C; the dissolution time can be 4 hours, 4.5 hours, 5 hours, 5.5 hours, 6 hours, 6.5 hours, 7 hours, 7.5 hours, or 8 hours; preferably, the dissolution temperature is 95°C and the dissolution time is 6 hours.

[0046] Thirdly, the present invention provides the application of the above-mentioned recombinant type III collagen bioadhesive or the recombinant type III collagen bioadhesive prepared by the above-mentioned preparation method in the preparation of minimally invasive postoperative tissue sealing products.

[0047] The recombinant type III collagen bioadhesive provided by this invention can rapidly gel and form a tightly adhered sealing layer on moist tissue surfaces. The minimally invasive postoperative tissue sealing products include, but are not limited to, lung wound sealing products after thoracoscopic wedge resection, liver wound sealing products after laparoscopic partial hepatectomy, and intestinal anastomosis sealing products. The bioadhesive can be used to seal air leakage between staples after lung resection, preventing pneumothorax and empyema; it can also be used to seal leakage from liver resection wounds or intestinal anastomoses, reducing the risk of secondary surgery.

[0048] In some embodiments of the present invention, the adhesion strength of the minimally invasive postoperative tissue sealing product on the surface of moist tissue can reach over 50 kPa, and the burst pressure can reach over 100 mmHg. Testing has shown that the burst pressure of the preferred embodiment of the present invention is significantly superior to commercially available fibrin glue and cyanoacrylate, effectively withstanding physiological pressure fluctuations (such as changes in intrathoracic pressure caused by respiratory movements), and providing a long-lasting airtight and leak-proof sealing effect.

[0049] In some embodiments of the present invention, the recombinant type III collagen bioadhesive exhibits significantly better cell survival rates in L929 cell survival tests than cyanoacrylate adhesives, and is comparable to or better than fibrin glue, indicating that it has good cell compatibility and safety in use.

[0050] The technical solution of the present invention will be further described below with reference to specific embodiments. The present invention does not impose any special restrictions on the source of reagents used in the following embodiments; commercially available products well known to those skilled in the art can be used.

[0051] Example 1 This embodiment provides a recombinant type III collagen bioadhesive, which is obtained by mixing and gelling a first component and a second component.

[0052] (1) Preparation of γ-polyglutamic acid modified with phenylboronic acid: To a 10 mg / mL aqueous solution of γ-polyglutamic acid, 100 mg / mL EDC·HCl and 100 mg / mL NHS solutions were added respectively at a mass ratio of γ-polyglutamic acid: EDC·HCl:NHS of 1:0.96:0.58. The mixture was stirred at room temperature for 30 minutes to activate the polyglutamic acid. Then, APBA·HCl solid was added to the above solution at a mass ratio of γ-polyglutamic acid to 3-aminophenylboronic acid salt (APBA·HCl) of 1:0.87. The mixture was stirred to dissolve, and the pH of the reaction solution was adjusted to 6.5 with 1 M NaOH. The reaction was carried out at room temperature in the dark for 24 h with stirring. After the reaction was completed, the reaction solution was transferred to a dialysis bag with a molecular weight cutoff of 3500 Da and dialyzed against deionized water containing 0.01 M HCl for 1 day, followed by dialyzed against deionized water for 2 days (the dialysate was changed every 8 hours, for a total of 9 times). The dialyzed solution was freeze-dried to obtain a white flocculent or spongy solid, which was phenylboronic acid-modified γ-polyglutamic acid.

[0053] (2) Preparation of the first component: The phenylboronic acid-modified γ-polyglutamic acid obtained in step (1) was dissolved in phosphate buffer (PBS, 0.01 M, pH 7.4) to prepare a 20 mg / mL solution, and stirred for 2 h until completely dissolved. Then, recombinant type III collagen lyophilized powder (amino acid sequence as shown in SEQ ID NO: 1) was slowly added to a final concentration of 5 mg / mL, and stirred at low speed for 4 h. The pH was precisely adjusted to 7.4 with 1 M NaOH to obtain the first component.

[0054] The recombinant type III collagen in this embodiment was prepared according to CN121873211B, and its amino acid sequence (SEQ ID NO: 1) is as follows: GlagypgpagppgppgerglpgppgekgetgepgprgergeagipgergapgekGlagypgpagppgppgerglpgppgekgetgepgprgergeagipgergapgek GlagypgpagppgppgerglpgppgekgetgepgprgergeagipgergapgekGlagypgpagppgppgerglpgppgekgetgepgprgergeagipgergapgek GlagypgpagppgppgerglpgppgekgetgepgprgergeagipgergapgekGlagypgpagppgppgerglpgppgekgetgepgprgergeagipgergapgek GlagypgpagppgppgerglpgppgekgetgepgprgergeagipgergapgekGlagypgpagppgppgerglpgppgekgetgepgprgergeagipgergapgek.

[0055] (3) Preparation of the second component: Polyvinyl alcohol powder was slowly added to PBS buffer (0.01 M, pH 7.4) to prepare a 10 wt% suspension. The suspension was heated to 95°C and stirred continuously for 6 h. After cooling naturally to room temperature, the second component was obtained.

[0056] (4) Obtaining bioadhesives: When using, take equal volumes of the first and second components, mix them evenly, and let them stand until they lose their fluidity to form a gel (about 1 min) to obtain recombinant type III collagen bioadhesive.

[0057] Example 2 The difference between this embodiment and Example 1 is that in this embodiment, the concentration of phenylboronic acid-modified γ-polyglutamic acid is increased to 40 mg / mL when preparing the first component, while the other steps and conditions remain unchanged.

[0058] Figure 1 This is a macroscopic photograph of the recombinant type III collagen bioadhesive prepared in this embodiment. Figure 1 In this context, A represents the initial image during the mixing process. Figure 1 Photo B in the image shows the state of the object after it has been laid flat and left to stand for about 5 seconds. It can be seen that gelation can be achieved in 5 seconds. Figure 1 C in the image shows the state of the bio-adhesive as it bends with the finger, demonstrating its good flexibility.

[0059] Example 3 The difference between this embodiment and Example 1 is that in this embodiment, the concentration of phenylboronic acid-modified γ-polyglutamic acid is increased to 60 mg / mL when preparing the first component, while the other steps and conditions remain unchanged.

[0060] Example 4 The difference between this embodiment and Example 1 is that, in this embodiment, the concentration of recombinant type III collagen is increased to 10 mg / mL when preparing the first component. The remaining steps and conditions remain unchanged.

[0061] Comparative Example 1 The difference between this comparative example and Example 1 is that this comparative example uses recombinant type III collagen with a different sequence. The recombinant type III collagen in this comparative example was prepared according to CN121873212B, and its amino acid sequence (SEQ ID NO: 2) is as follows: GMEGERGEDGHRGFDGRNGAPGERGRPGLPGEKGENGLDGLPGERGENGAPGPMGPRGAPGERGRPGLPGERGENGAPGEKGLPGLKGENGLPGENGAPGDPGRPGDRGEKGHRGFDGRNGEKGAPGERGRPGLPGENGAPGPMGPRGAPGERGENGAPGERGPRGAPGLD.

[0062] In this comparative example, after equal volumes of the first and second components were mixed uniformly, the mixture showed a heterogeneous, agglomerated complex with phase separation, such as... Figure 2 As shown, its texture is fragile and brittle, making it impossible to conduct normal mechanical tests. It does not possess actual wound adhesion and sealing properties, therefore no further tests were conducted.

[0063] Comparative Example 2 The difference between this comparative example and Example 1 is that, in this comparative example, the final concentration of recombinant type III collagen was increased to 20 mg / mL when preparing the first component. The specific steps are as follows: (1) Preparation of γ-polyglutamic acid modified with phenylboronic acid: γ-polyglutamic acid modified with phenylboronic acid was prepared using the same method as step (1) of Example 1.

[0064] (2) Preparation of the first component: The phenylboronic acid-modified γ-polyglutamic acid obtained in step (1) was dissolved in phosphate buffer (PBS, 0.01 M, pH 7.4) to prepare a 20 mg / mL solution, and stirred for 2 h until completely dissolved. Then, recombinant type III collagen lyophilized powder (amino acid sequence as shown in SEQ ID NO: 1) was slowly added to a final concentration of 20 mg / mL. After stirring at low speed for 4 h, the recombinant type III collagen still could not be completely dissolved, the solution became turbid and produced particulate precipitates. The first component was in a heterogeneous suspension state and could not be used as an effective component to participate in the subsequent gelation process and performance test.

[0065] Comparative Example 3 The difference between this comparative example and Example 1 is that no recombinant type III collagen was added when preparing the first component in this comparative example, while the remaining steps and conditions remained unchanged.

[0066] Comparative Example 4 The adhesive used in this comparative example is a commercially available cyanoacrylate adhesive (purchased from Beijing Kangpaite Medical Devices Co., Ltd.).

[0067] Comparative Example 5 The adhesive used in this comparative example was commercially available fibrin glue (purchased from Harbin Hanbang Medical Technology Co., Ltd.).

[0068] Test case 1. Scanning electron microscopy analysis The internal structure of the bio-adhesive was examined using a scanning electron microscope. Prior to the examination, the bio-adhesive was freeze-dried and plated with gold.

[0069] like Figure 3 As shown, under a scanning electron microscope, the lyophilized bioadhesive of Example 2 exhibits a highly interconnected, interpenetrating three-dimensional porous sponge-like network structure. The internal pores of the gel are irregularly streamlined or elongated elliptical, with a uniform pore size distribution and continuous, intact pore walls. This interconnected and open porous morphology facilitates the formation of a mechanical interlock between the bioadhesive and the moist tissue surface, enhancing interfacial adhesion; simultaneously, the continuous and intact pore wall structure endows the gel with good structural integrity, which is beneficial for forming a continuous covering layer on the wound surface and exerting a sealing effect.

[0070] 2. Adhesion performance test To evaluate the adhesion performance of the bio-adhesive of the present invention to tissues, the bio-adhesives of different embodiments and comparative examples were subjected to porcine skin shear adhesion strength tests. The surface was moistened with physiological saline to simulate the real wet state of the surgical wound. After the adhesive was bonded to the porcine skin surface, a shear force parallel to the bonding surface was applied. The test speed was 10 mm / min, and three samples were tested in each test.

[0071] Shear adhesion strength test results are as follows Figure 4As shown. A comparison of Examples 1 and 4 shows that, with the concentration of phenylboronic acid-modified γ-polyglutamic acid remaining constant, appropriately increasing the concentration of recombinant type III collagen did not significantly change the wet adhesion strength, indicating that the amount of collagen used in Example 1 was sufficient for interfacial adhesion. A comparison of Example 1 and Comparative Example 3 shows that removing the recombinant type III collagen significantly reduced the wet adhesion strength. Furthermore, a comparison of Example 1 and Comparative Example 1 shows that not all types of recombinant type III collagen are suitable for this system; collagen with incompatible sequence characteristics will lead to phase separation and heterogeneous aggregation, preventing normal gelation. A comparison of Examples 1-3 shows that appropriately increasing the concentration of phenylboronic acid-modified γ-polyglutamic acid can further improve the wet adhesion strength, but excessively high concentrations result in a significant decrease in adhesion strength, indicating that appropriately increasing the crosslinking density helps enhance gel cohesion and stress transfer ability, but excessively high crosslinking density leads to brittleness of the gel network.

[0072] 3. Bursting pressure A burst pressure testing device was prepared, comprising a sealable flange with a pressurization port at the bottom and a circular hole with a diameter of 5 cm at the top. Fresh isolated mammalian lung tissue was taken, covered, and fixed onto the hole at the top of the flange. A through-hole circular defect with a diameter of 1 cm was created in the center of the tissue using a punch. The defect surface was moistened with physiological saline. The mixture of Examples 1-4 and Comparative Example 3, as well as the adhesive samples of Comparative Examples 4 and 5, were applied to the defect, completely covering the defect area (approximately 4 cm in diameter), and allowed to stand for 30 seconds. The sealing flange was assembled, and a microfluidic injection pump was connected to inject air into the flange at a constant rate of 10 mL / min, while observing the adhesive sealing layer. When the adhesive was ruptured by the airflow, the maximum pressure value displayed on the pressure gauge was recorded, which is the burst pressure.

[0073] Experimental results are as follows Figure 5 As shown. A comparison of Examples 1 and 4 shows that, with the concentration of phenylboronic acid-modified γ-polyglutamic acid remaining constant, appropriately increasing the concentration of recombinant type III collagen did not significantly change the burst pressure, indicating that the amount of collagen used in Example 1 was sufficient to meet the pressure resistance requirements of the sealing layer. A comparison of Example 1 and Comparative Example 3 shows that removing the recombinant type III collagen significantly reduced the burst pressure. Based on this, a comparison of Examples 1-3 shows that appropriately increasing the concentration of phenylboronic acid-modified γ-polyglutamic acid can further increase the burst pressure, but excessively high concentrations result in a significant decrease in burst pressure. Furthermore, compared to commercially available cyanoacrylate adhesives (Comparative Example 4) and fibrin adhesives (Comparative Example 5), the bio-adhesive prepared using the specific formulation in this invention exhibits significantly superior burst pressure, which contributes to the adhesive's durability and better performance in terms of airtightness and leak-proof sealing.

[0074] 4. Cell viability To investigate the effect of recombinant type III collagen on cell compatibility, CCK-8 cell viability was compared between the bioadhesives of different examples and comparative examples, as well as the commercially available cyanoacrylate adhesive of Comparative Example 4 and the commercially available fibrin glue of Comparative Example 5. The bioadhesives were extracted at 0.2 g / mL in complete culture medium at 37°C for 24 h, filtered through a sterile filter membrane, and the extract was prepared for use. 100 μL of cell suspension (containing 1×10⁻⁶ cells / mL) was added to each well of a 96-well plate. 4 (100 L929 cells) were cultured for 24 h to allow cell adhesion. The old culture medium was removed, and 100 μL of bio-adhesive extract was added to each well. The control group received an equal volume of complete culture medium. After culturing for another 72 h, 10% (v / v) of CCK-8 solution was added to each well, gently shaken to mix, and incubated statically for another 2 h. The absorbance at 450 nm was measured using a microplate reader, and cell viability was calculated.

[0075] Cell viability test results as follows Figure 6 As shown in the figures, the cell viability rates of Examples 1, 2, and 4 were all superior to those of fibrin-based adhesives, and the values ​​were similar across the three examples. This indicates that once recombinant type III collagen reaches an effective concentration, it can fully exert its cell proliferation-promoting effect, and further increasing the concentration does not further improve cell compatibility. A comparison between Example 1 and Comparative Example 3 shows that the cell viability rate decreased significantly after removing recombinant type III collagen, indicating that collagen plays an indispensable role in maintaining good cell compatibility of the adhesive. A comparison between Example 2 and Example 3 shows that the cell viability rate decreased when the concentration of phenylboronic acid-modified γ-polyglutamic acid was too high, indicating that excessively high crosslinking density is not conducive to the effective release of the active ingredients. Furthermore, compared with commercially available cyanoacrylate adhesives (Comparative Example 4), the cell viability rates of all examples of this invention are significantly superior, indicating that the bio-adhesive of this invention has higher cell safety.

[0076] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A recombinant type III collagen bioadhesive, characterized in that, It is obtained by gelling a mixture of the first and second components; The first component comprises phenylboronic acid-modified γ-polyglutamic acid and recombinant type III collagen; The second component includes polyvinyl alcohol; The phenylboronic acid-modified γ-polyglutamic acid was prepared by grafting 3-aminophenylboronic acid onto γ-polyglutamic acid via an amidation reaction; the amino acid sequence of the recombinant type III collagen is shown in SEQ ID NO:

1.

2. The recombinant type III collagen bioadhesive as described in claim 1, characterized in that, In the first component, the concentration of phenylboronic acid-modified γ-polyglutamic acid is 20~60 mg / mL, and the concentration of recombinant type III collagen is 1~15 mg / mL.

3. The recombinant type III collagen bioadhesive as described in claim 1, characterized in that, In the second component, the concentration of polyvinyl alcohol is 5~15 wt%.

4. The method for preparing the recombinant type III collagen bioadhesive according to any one of claims 1 to 3, characterized in that, Includes the following steps: Phenylboronic acid-modified γ-polyglutamic acid and recombinant type III collagen were dissolved in the first buffer solution to obtain the first component; Polyvinyl alcohol was dissolved in the second buffer solution and heated and stirred until completely dissolved to obtain the second component; The first component and the second component are mixed and allowed to gel at rest to obtain the recombinant type III collagen bioadhesive.

5. The preparation method according to claim 4, characterized in that, The first buffer and the second buffer are each independently selected from at least one of phosphate buffer, 4-hydroxyethylpiperazine ethanesulfonic acid buffer or tris(hydroxymethyl)aminomethane hydrochloride buffer; the pH of the first buffer and the second buffer is 7.2 to 7.

6.

6. The preparation method according to claim 4, characterized in that, The preparation method of the phenylboronic acid modified γ-polyglutamic acid is as follows: γ-polyglutamic acid is dissolved in a solvent, activated by adding an activator, and then 3-aminophenylboronic acid or its salt is added for amidation reaction. After dialysis and freeze drying, phenylboronic acid modified γ-polyglutamic acid is obtained.

7. The preparation method according to claim 6, characterized in that, The mass ratio of γ-polyglutamic acid and 3-aminophenylboronic acid or their salts is 1:(0.6~1.2); the activator is 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide; the mass ratio of γ-polyglutamic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide is 1:(0.8~1.2):(0.4~0.8).

8. The preparation method according to claim 6, characterized in that, The amidation reaction takes 15-30 h, is carried out at 15-40 °C, and has a pH of 6.2-6.

8. The amidation reaction is conducted under light-protected conditions.

9. The preparation method according to claim 4, characterized in that, The mixing volume ratio of the first component to the second component is 1:(0.8~1.2).

10. The application of the recombinant type III collagen bioadhesive as described in any one of claims 1 to 3 or the recombinant type III collagen bioadhesive prepared by the preparation method described in any one of claims 4 to 9 in the preparation of minimally invasive postoperative tissue sealing products.

Citation Information

Patent Citations

  • Recombinant humanized type III collagen, preparation methods and applications

    CN121873211B

  • Recombinant humanized type III collagen containing a triple helix structure, its preparation method and application

    CN121873212B